Applied of Analytical Hierarchy Process and Fuzzy Time Series in Hybrid for Optimizing Smart Vertical Farming with Multi-Variety Plants - Wibowo, Danang Arengga; Sendari, Siti; Wibawa, Aji Prasetya; Wibowo, Fauzy Satrio (International Journal of Artificial Intelligence Research, 2023)
Vertical Farming is a kind of modern agricultural methods, where the structure of growing racks are arranged upwards. This method aims to optimize the use of agricultural space. There are many plants, which are suitable to be planted for vertical farming, such as Strawberry, Tomatoes, Celery, Chili, Mint, Chives, Kuchay, Spinach, and Water spinach. The problem, which is studied in this paper, is how to control the environments of vertical farming with multi-variety plants. This paper proposed a hybrid method of Analytical Hierarchy Process and Fuzzy Time Series AHP-FTS, that is, plants with similar characteristics are placed at the same block area determined by the method of Analytical Hierarchy Process (AHP). Furthermore, controlling the environments regarding the needs of appropriate growing parameters for multi-variety plants, the Fuzzy Time Series (FTS) method is used. Then, time variable for activating actuators could be adjusted as a multi-control system. The effectiveness of the proposed method was evaluated with 365 record data in 12 months. The result shows that the AHP was successful to determine the multi-criteria to determine the zone and priority of plants. The second stage is that the FTS predicts the temperature to determine time variable for activating actuators, and the third stage is the implemented AHP-FTS as a hybrid system to evaluate the vertical Farming system. The results show that the proposed system works well as hybrid system of AHP-FTS